Effect of natural full weight‐bearing during standing on the rotation of the first metatarsal bone. Issue 5 (29th April 2019) - Ota, Tomohiko; Nagura, Takeo; Yamada, Yoshitake; Yamada, Minoru; Yokoyama, Yoichi; Ogihara, Naomichi; Matsumoto, Morio; Nakamura, Masaya; Jinzaki, Masahiro
Abstract : To evaluate the rotational change in the first metatarsal bone (1MT) of the foot during natural standing using an upright computed tomography (CT) scanner with 320‐detector rows. A total of 52 feet of 28 asymptomatic subjects (aged 23–39 years) were evaluated in the natural standing position with or without weight‐bearing. A foot pressure plate was used to determine the non‐weight‐bearing (NWB) or single leg full‐weight‐bearing (s‐FWB) conditions. CT examinations were performed using a noise index of 15 for a slice thickness of 5 mm, rotation speed of 0.5 sec, and slice thickness of 0.5 mm. The rotation of the 1MT was measured on the coronal CT image, which cut the sesamoids' bellies in the frontal slide of the first metatarsal and sesamoids perpendicular to the longitudinal bisection of the third metatarsal, and compared between the weight‐bearing conditions. Intra‐ and inter‐observer reliabilities of the rotation angle were also evaluated. The intra‐ and inter‐observer correlation coefficients were 0.961 and 0.934, respectively. The 1MT pronation angle was significantly greater in the s‐FWB condition than in the NWB condition (15.2° ± 5.4° vs. 12.5° ± 5.3°, P  < 0.01). No sex difference was found in the magnitude of the 1MT pronation angle as a result of weight‐bearing. This study first demonstrated that pronation of 1MT occurs due to natural full‐weight‐bearing in asymptomatic feet. The 1MT's rotational movement under weight‐bearing conditions may relate to the onset and pathogenesis of the hallux valgus. Clin. Anat. 32:715–721, 2019. © 2019 Wiley Periodicals, Inc.